Application of The Drill Method to Improving Science Learning Outcomes - Sudirman Sudirman; Moh. Irawan Zain (Jurnal Penelitian Pendidikan IPA, 2023)
The purpose of this study is to describe the application of the drill method in teaching science at the same time knowing the goodness drill method on learning outcomes of students. Subjects chosen because statistics by developing the notion among students that this course is difficult to understand at once a few of those who obtain superior value (A). Through the pre-experimental study, one group pretest-posttest design in the sixth semester students of class D PGSD FKIP Unram regular afternoon, with 44 samples of 50 students purposive random sampling. Performed drill application of the method to the class VI/D through the afternoon, integrative stage, fixation and autonomous learning statistics. The mean pretest and posttest results to the 44 students of the samples obtained through three implementation pretest and posttest then compared. The results showed a mean posttest learning outcomes (69.41) is better than the average learning outcomes pretest (53.05). Test results found the normalized gain <g> g = 0.348 (moderate classification). Indicated drill method can improve student learning outcomes statistics, indicated by differences in learning outcomes and pretest posttest at 16.36 and significant in the medium category